The Dynamic Effect of Public Information on Liquidity: From the Perspective of Limited Attention. (28th June 2021) - Bing, Tao; Cui, Yian
Abstract : The financial system is a complex system. The heterogeneous behaviors of investors further increase the degree of its complexity. In this paper, we develop a rational expectations equilibrium model to analyze the effect of public information on market efficiency and liquidity, especially in the market in which investors monitor the market imperfectly. When public information is partly reflected in equilibrium price or the uncertainty about the asset value is great, market efficiency increases with the increase of the precision of public information and the investors holding it. However, when the uncertainty about the fundamental value is small, the increase of the precision of public information worsens market liquidity. And in this market, with the increase of the investors acquiring public information, market liquidity first decreases and then increases. Overall, our results suggest that listed companies should disclose their information accurately by different channels as much as possible, and the regulators should enhance the supervision of information disclosure to enhance market efficiency and liquidity.